Designing ultra-highly efficient Mn2+-activated Zn2GeO4 green-emitting persistent phosphors toward versatile applications. (March 2022) - Xue, J.; Li, F.; Liu, F.; Noh, H.M.; Lee, B.R.; Choi, B.C.; Park, S.H.; Jeong, J.H.; Du, P.
Abstract: Developing highly efficient green-emitting phosphors is very significant because human eyes are sensitive to green spectral region. Herein, Mn 2+ -activated Zn2 GeO4 phosphors, which can emit bright green light with an ultrahigh internal quantum efficiency of 98.5%, were prepared by a solid-state reaction technology in ambient atmosphere. At 323 nm irradiation, the emission spectrum shows a narrow band centered at 534 nm, which is ascribed to the 4 T1 → 6 A1 transition of Mn 2+, with a full width at half maxima of 49.5 nm. Through monitoring the temperature-dependent photoluminescence emission intensity and decay time of Mn 2+, we explored the thermometric properties of the resultant compound and found maximum relative sensitivities of Zn2 GeO4 :0.02Mn 2+ phosphor are 4.90% K −1 and 0.74% K −1, respectively. Furthermore, green afterglow phenomenon is observed in the designed phosphors, and its mechanism is verified by discussing the thermoluminescence. Because of the excellent luminescence behaviors, various multimode luminescent patterns for information encryption are designed, including anticounterfeiting and fingerprint identification. Furthermore, using the prepared Zn2 GeO4 :0.02Mn 2+ as green-emitting components, a white-light-emitting diode with suitable color coordinates, high color rending index (>90), and low correlated color temperature (5, 000–6, 000 K) was fabricated. These results demonstrate that Mn 2+ -activated Zn2 GeO4 phosphors are multifunctional green-emitting components for optical thermometry, anticounterfeiting, fingerprint detection, and solid-state lighting applications. Highlights: Zn2 GeO4 :Mn 2+ phosphors present bright green emission with internal quantum efficiency of 98.5%. Using the photoluminescence intensity of Mn 2+ in various temperature, the maximum S r is 4.90% K −1 . Using lifetime of Mn 2+ in various temperature, the maximum S r is 0.74% K −1 . Multimode luminescent patterns for information encryption are designed. A white-light-emitting diode with suitable color coordinates, high Ra, and low correlated color temperature values was fabricated.